2006
DOI: 10.1249/01.mss.0000210195.94952.50
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Reduces Serum Prolactin Increase Induced by Exercise to Exhaustion

Abstract: The present study suggests that acidosis is a stimulus for exercise-induced PRL secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…Several studies investigated the effects of system fatigue on running mechanics [25, 26] but the causes of the terminal running speed drop remained unknown. It has been established that exhaustive supramaximal exercise induced a significant decrease in capillary blood bicarbonate concentration (HCO 3 − ), pH, base excess (BE), and carbon dioxide partial pressure (PCO 2 ) at exhaustion and during the recovery period [14]. Recently, a negative correlation was found between running performance, muscular pH, and lactate accumulation rates [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the effects of system fatigue on running mechanics [25, 26] but the causes of the terminal running speed drop remained unknown. It has been established that exhaustive supramaximal exercise induced a significant decrease in capillary blood bicarbonate concentration (HCO 3 − ), pH, base excess (BE), and carbon dioxide partial pressure (PCO 2 ) at exhaustion and during the recovery period [14]. Recently, a negative correlation was found between running performance, muscular pH, and lactate accumulation rates [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exhaustive supramaximal exercise induced a significant decrease in capillary blood bicarbonate concentration (HCO 3 − ), pH, base excess (BE), and carbon dioxide pressure (PCO 2 ) at exhaustion and during the recovery period [14, 15] which could affect muscle contracting activity and metaboreflex responses compared to aerobic exercise. It has been also reported that high exercise intensity experienced by weightlifters caused muscle's exposure to the products of anaerobic metabolism and a delayed vagal response [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, stress and physical activity are neurobiological counter-players [5, 6], and stress reduction through exercise not only improves memory functions, hippocampal neurogenesis and BDNF levels, but also mood, quality of life, and overall well-being [5, 12, 52, 56]. However, this seems to apply only to moderate exercise, since prolonged and strenuous physical activity, for example, can itself cause stress and proinflammation [57–61]. Besides the prefrontal or orbitofrontal and hippocampal areas of the brain, there are other regions that also seem to be of importance in the neurobiological stress-SM-exercise-cognition relationship, e.g., temporal cortex, bilateral insula and parainsular cortex, as well as temporoparietal regions, the amygdala and anterior cingulate, yet again suggesting region-specific effects in frontolimbic brain areas that are also involved in the processing of affective states and mood [5, 36, 40, 52, 56].…”
Section: Stress Reduction Exercise Brainmentioning
confidence: 99%
“…The opioid peptides β-endorphin and Met-enkephalin with its precursor proenkephalin originate from the anterior pituitary, where proopiomelanocortin (POMC) is produced, again showing the connection between this signalling system and the central stress axes, as illustrated. Interestingly, prolactin is also enhanced during and post-exercise, comparable to cortisol, however, this latter hormone is a partial dopamine inhibitor that comes consecutively (i.e., delayed) after dopamine release in the stress-exercise sequence was initiated [61], comparable to the endorphins [5]. Prolactin also originates from the anterior pituitary.…”
Section: Stress Reduction Exercise Brainmentioning
confidence: 99%
See 1 more Smart Citation